Quality of life epilepsy in childhood: Comparison between well-controlled epilepsy and non epilepsy - Soeroyo Machfudz, Fita Wirastuti Suryono Yudha Patria (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Quality of life is an important parameter in assessing the efficacy of medical interventions. Chronic diseases such asepilepsy, have a significant impact on quality of life. Childhood epilepsy is often associated with low achievement inschool, physical limitations, and disturbed social functions. The purpose of this study was to compare the quality oflife of well-controlled epileptic children with non epileptic children. This research was conducted with cross-sectionalstudy design with respondents aged 5-18 years old. All respondents were well-controlled epileptic and non epilepticchildren who were admitted to the Pediatric Polyclinic of Dr. Sardjito General Hospital, Yogyakarta, Indonesia in theperiod of March until June 2010. Measurement of quality of life was conducted by filling out the questionnairePediatrics Quality of Life (PedsQL) that directly obtained from the children who were accompanied by their parent.Lower total score of PedsQL showed better quality of life. The results showed that mean total score of PedsQL onwell-controlled epileptic children (38.31Â±1.6) was higher than non epileptic children (8.84Â±0.90). Prevalence ratioof controlled epileptic children was 2.69 (95% CI: 2.01-3.58). In conclusion, well-controlled epileptic children hadlower quality of life than non epileptic children. The factors that affect quality of life of well-controlled epilepticchildren were duration of suffering from epilepsy and age at diagnosis of epilepsy.Key words: quality of life â well-controlled epileptic children - PedsQL â physical function â emotional functionsocialfunction